Characterization And Ochratoxin ‘A’ Production Of Aspergillus Section Nigri - Rahman, Wardah Abdul (2019)
Several species of black Aspergillus or Aspergillus section Nigri can act as saprophytes as well as contaminants of food and feed. There are also black Aspergillus that are toxigenic, producing ochratoxin A (OTA) which is a mycotoxin known to be associated with food and feed. This toxin can cause adverse effects to humans and animals. The aims of this present study were to accurately identified and characterize black Aspergillus from various substrates and indoor environment in Malaysia, to determine the phylogenetic relationships between the species, to characterize the species using Restriction Fragment Length Polymorphism (RFLP) technique of internal transcribed spacer regions (ITS) and to determine the ability of the species to produce OTA. In this study, 177 isolates of black Aspergillus from food (rice, groundnuts and spices), feed (corn grains), soil and indoor environment were morphologically identified as A. niger (153 isolates) and A. aculeatus (24 isolates). Based on sequences of ITS, β-tubulin and calmodulin, the species were re-identified as A. niger (144 isolates), A. aculeatus (24 isolates) and A. tubingensis (nine isolates). Phylogenetic analysis of individual and combined ITS, β-tubulin and calmodulin sequences using Neighbour-joining and Maximum Likelihood methods showed that A. niger, A. aculeatus and A. tubingensis were clustered according to the species.